Pharmacogenomic interaction between the Haptoglobin genotype and vitamin E on atherosclerotic plaque progression and stability. Issue 1 (March 2015) - Viener, Hilla-Lee; Gorbatov, Rostic; Vardi, Moshe; Doros, Gheorghe; Miller-Lotan, Rachel; Zohar, Yaniv; Sabo, Edmond; Asleh, Rabea; Levy, Nina S.; Goldfarb, Levi J.; Berk, Thomas A.; Haas, Tali; et al.
Abstract: Objective: Homozygosity for a 1.7 kb intragenic duplication of the Haptoglobin (Hp) gene (Hp 2-2 genotype), present in 36% of the population, has been associated with a 2–3 fold increased incidence of atherothrombosis in individuals with Diabetes (DM) in 10 longitudinal studies compared to DM individuals not homozygous for this duplication (Hp 1-1/2-1). The increased CVD risk associated with the Hp 2-2 genotype has been shown to be prevented with vitamin E supplementation in man. We sought to determine if there was an interaction between the Hp genotype and vitamin E on atherosclerotic plaque growth and stability in a transgenic model of the Hp polymorphism. Methods and Results: Brachiocephalic artery atherosclerotic plaque volume was serially assessed by high resolution ultrasound in 28 Hp 1-1 and 26 Hp 2-2 mice in a C57Bl/6 ApoE −/− background. Hp 2-2 mice had more rapid plaque growth and an increased incidence of plaque hemorrhage and rupture. Vitamin E significantly reduced plaque growth in Hp 2-2 but not in Hp 1-1 mice with a significant pharmacogenomic interaction between the Hp genotype and vitamin E on plaque growth. Conclusions: These results may help explain why vitamin E supplementation in man can prevent CVD in Hp 2-2 DM but not in non Hp 2-2 DM individuals. Highlights: Plaque volume can be assessed serially in the same mouse over time by high resolution ultrasound. Hp genotype is a determinant of atherosclerotic plaque volume growth development. Hp 2-2 plaques have more unstable features including more iron, thinner caps and more hemorrhage. Vitamin E is decreased in Hp 2-2 plasma. Vitamin E can prevent plaque volume growth in Hp 2-2 mice.